Transformational Leadership and Organizational Commitment among Generation Z Employees in Indonesia - Marhisar Simatupang; Rina Anindita; Winanti Siwi Respati (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
High employee mobility among Generation Z has emerged as a critical human resource challenge in Indonesia. This study investigates the direct influence of transformational leadership on organizational commitment among Generation Z employees. Using a quantitative correlational design, data were collected from 410 Generation Z workers across various industrial sectors in Indonesia. Transformational leadership was measured using the Bass and Avolio framework, while organizational commitment was assessed using an adapted Meyer and Allen scale. Data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results indicate that transformational leadership has a significant and positive effect on organizational commitment (β = 0.72; p < 0.001), explaining 52.8% of the variance in commitment. These findings demonstrate that transformational leadership plays a crucial role in fostering emotional attachment and loyalty among Generation Z employees. This study contributes to the literature by providing empirical evidence focused exclusively on Generation Z within a developing country context.